Local Community In The Management Of Tanjung Rejo Tourist Village, Percut Sei Tuan District - devy meylani rajagukguk (Wonderful-Journal of Tourism Destination, 2026)
This study aims to analyze community involvement in the management of Tanjung Rejo Tourism Village and to formulate empowerment strategies to enhance participation in community-based tourism development. Although the village holds great potential through its extensive mangrove ecosystem, local participation remains low. Using a qualitative approach and case study method, data were collected through observation, in- depth interviews, and documentation, and analyzed using the Miles and Huberman model as well as a SWOT matrix. The findings reveal that limited community involvement is due to a lack of information, training, and access to resources. Recommended empowerment strategies include continuous training, strengthening local institutions  such  as  BUMDes  and  tourism  awareness  groups,  and  fostering  collaboration  with  external stakeholders. This study is expected to serve as a reference for developing more inclusive andsustainable tourism village policies.